Physiological impacts and bioaccumulation of dietary Cu and Cd in a model teleost: The Amazonian tambaqui (Colossoma macropomum) - Giacomin, Marina; Vilarinho, Gisele C.; Castro, Katia F.; Ferreira, Márcio; Duarte, Rafael M. [UNESP]; Wood, Chris M.; Val, Adalberto L. (Elsevier, 2018)
Increasing anthropogenic activities in the Amazon have led to elevated metals in the aquatic environment. Since fish are the main source of animal protein for the Amazonian population, understanding metal bioaccumulation patterns and physiological impacts is of critical importance. Juvenile tambaqui, a local model species, were exposed to chronic dietary Cu (essential, 500 μg Cu/g food) and Cd (non-essential, 500 μg Cd/g food). Fish were sampled at 10–14, 18–20 and 33–36 days of exposure and the following parameters were analyzed: growth, voluntary food consumption, conversion efficiency, tissue-specific metal bioaccumulation, ammonia and urea-N excretion, O2 consumption, Pcrit, hypoxia tolerance, nitrogen quotient, major blood plasma ions and metabolites, gill and gut enzyme activities, and in vitro gut fluid transport. The results indicate no ionoregulatory impacts of either of the metal-contaminated diets at gill, gut, or plasma levels, and no differences in plasma cortisol or lactate. The Cd diet appeared to have suppressed feeding, though overall tank growth was not affected. Bioaccumulation of both metals was observed. Distinct tissue-specific and time-specific patterns were seen. Metal burdens in the edible white muscle remained low. Overall, physiological impacts of the Cu diet were minimal. However dietary Cd increased hypoxia tolerance, as evidenced by decreased Pcrit, increased time to loss of equilibrium, a lack of plasma glucose elevation, decreased plasma ethanol, and decreased NQ during hypoxia. Blood O2 transport characteristics (P50, Bohr coefficient, hemoglobin, hematocrit) were unaffected, suggesting that tissue level changes in metabolism accounted for the greater hypoxia tolerance in tambaqui fed with a Cd-contaminated diet.
Keywords: Dietary metals; Hypoxia; Pcrit; Tissue accumulation; Tropical teleost